2007
DOI: 10.1139/x07-063
|View full text |Cite
|
Sign up to set email alerts
|

Forest soil rehabilitation with tillage and wood waste enhances seedling establishment but not height after 8 years

Abstract: We evaluated soil conditions of rehabilitated log landings in the Interior Douglas-fir biogeoclimatic zone of British Columbia during the first 3 years after treatment and the growth of lodgepole pine ( Pinus contorta Dougl. ex Loud. var. latifolia Engelm.) on these log landings over 8 years. Rehabilitation treatments included combinations of tillage and the addition of either stockpiled topsoil or one of three organic amendments: hog fuel, sort-yard waste, and a wood waste – biosolids compost. The woody amend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Indeed, incorporation of wood can enhance several important soil properties. Surface applications, such as mulch used in landscaping and coarse woody debris on forest floors (Bulmer et al ), have been shown to increase soil moisture. Less is known about the role or mechanisms by which incorporation of coarse wood chips into the soil can influence soil moisture regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, incorporation of wood can enhance several important soil properties. Surface applications, such as mulch used in landscaping and coarse woody debris on forest floors (Bulmer et al ), have been shown to increase soil moisture. Less is known about the role or mechanisms by which incorporation of coarse wood chips into the soil can influence soil moisture regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Log yard fines (LYF) can increase water holding capacity and porosity [6] but have also been shown to reduce crop performance due to nitrogen immobilization [7]. For this reason, biosolids are often mixed with LYF and other wood byproducts as a means to reduce C : N and maintain nitrogen availability [8,9]. Others have utilized agricultural limestone or wood ash in biosolids mixtures to reduce metal bioavailability [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…These areas may be unproductive unless soil rehabilitation is carried out. Trees growing on compacted soil are generally characterized by reduced root elongation (Whalley et al 1995) and, sometimes, by reduced height growth (Greacen and Sands 1980;Ares et al 2007;Bulmer et al 2007), but predictability varies. The variation in tree growth responses reported in different studies could have been caused by selection of compaction indicators that were not always successful in describing the relationship between soil compaction and tree growth or by the fact that compaction treatments did not reach growth-limiting levels in some studies.…”
Section: Introductionmentioning
confidence: 99%